Social anxiety and disordered eating: The influence of stress reactivity and self-esteem. (August 2017) - Ciarma, Jessica Lyn; Mathew, Jaya Miriam
Abstract: While previous research indicates a strong link between social anxiety and disordered eating, more research is needed in order to understand the mechanisms that underlie this relationship. Given that stress is often implicated in disordered eating, it was hypothesised that ones reaction to stress (i.e. stress reactivity) would mediate the relationship between social anxiety and disordered eating. Similarly, given that low self-esteem is commonly reported in both those with social anxiety and eating disorders, it was hypothesised that self-esteem would also mediate the relationship between social anxiety and disordered eating. In order to test this, an online survey measuring social anxiety, disordered eating, stress reactivity and self-esteem, was administered to 282 participants in the community, aged between 18 and 35 years. Results showed that self-esteem and a reactivity to stress during social conflict – but not during negative social evaluations – partially mediated the relationship between social anxiety and disordered eating. These findings demonstrate that low self-esteem and interpersonal conflict are powerful mechanisms that can maintain eating disorder psychopathology in those who are socially anxious. This highlights the importance of ensuring that these mechanisms are sufficiently addressed in eating disorder prevention and treatment programs. Highlights: Research exploring mechanisms that explain the relationship between social anxiety and disordered eating is needed. Self-esteem and stress reactivity were tested as potential mediators of the social anxiety-disordered eating relationship. Self-esteem and stress reactivity partially mediated the relationship between social anxiety and disordered eating. These mediators should be considered during screening and treatment for disordered eating.